Metals levels and human health risk assessment in eight commercial fish species collected from a market, Wuhan, China - Yin, Jiaojiao; Cheng, Liangyu; Jiang, Xiaoming; Wang, Li; Gao, Pan; Zhong, Wu; Zhang, Xuezhen (Frontiers in Sustainable Food Systems, 2024)
Introduction Heavy metals are ubiquitous environmental pollutants, and fish could be contaminated by these metals, potentially posing a threat to human health through the food chain. Understanding the accumulation of these metals in fish tissues is crucial for assessing the safety of consuming fish products. Methods In this study, the distribution of nickel (Ni), copper (Cu), zinc (Zn), cadmium (Cd), and lead (Pb) in tissues of eight fish species (Ctenopharyngodon idellus, Megalobrama amblycephala, Hypophthalmichthys molitrix, Hypophthalmichthys nobilis, Carassius auratus, Cyprinus carpio, Culter alburnus, and Lateolabrax japonicas) collected from the Baishazhou market with different trophic levels and habitat preference was investigated using inductively coupled plasma mass spectrometry (ICP-MS). The metal accumulation capacity of different fish tissues and species was assessed, and the metal pollution index (MPI) was calculated to evaluate the extent of metal accumulation ability in each species. Additionally, the health risk assessment was conducted to evaluate the potential threat to human health posed by consuming these fish species. Results The levels of metals exhibited variation among different fish tissues and species, showing an order of Zn > Cu > Ni > Pb > Cd. In terms of tissues, fish head demonstrated a greater capacity for metal accumulation compared to the muscles. Regarding fish species, the extent of accumulation ability varied depending on the specific metal, exhibiting the following order according to MPI: H. molitrix (0.568) > C. auratus (0.508) > M. amblycephala (0.469) > C. idellus (0.336) > C. alburnus (0.315) > C. carpio (0.274) > L. japonicus (0.263) > H. nobilis (0.206). Furthermore, in accordance with the results of health risk assessment, there was no potential health risk associated with the consumption of these fish species, as all target hazard quotient (THQ) values (ranger from not detected to 0.192) were below 1, and the maximum hazard index (HI) value was observed in C. carpio (0.519 for adults, 0.622 for children). Conclusion The findings of this study demonstrate the distribution of heavy metals in fish tissues and indicate there were no potential health risk associated with consuming these fish bought from the Baishazhou market.